Making 'Math Making' Virtual - Candace Figg; Anjali Khirwadkar; Shannon Welbourn (Brock University, 2020)
Due to the COVID-19 pandemic, university professors are challenged to re-envision mathematics learning environments for virtual delivery. Those of us teaching in elementary teacher preparation programs are exploring different learning environments that not only promote meaningful learning but also foster positive attitudes about mathematics teaching. One learning environment that has been shown to be effective for introducing preservice teachers to the creative side of mathematics-the mathematics makerspace-promotes computational thinking and pedagogical understandings about teaching mathematics, but the collaborative, hands-on nature of such a learning environment is difficult to simulate in virtual delivery. This article describes the research-based design decisions for the re-envisioned virtual mathematics makerspace.